2011
DOI: 10.1186/1479-5876-9-76
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with vemurafenib (PLX4032/RG7204) and metformin in melanoma cell lines with distinct driver mutations

Abstract: BackgroundA molecular linkage between the MAPK and the LKB1-AMPK energy sensor pathways suggests that combined MAPK oncogene inhibition and metabolic modulation of AMPK would be more effective than either manipulation alone in melanoma cell lines.Materials and methodsThe combination of the BRAF inhibitor vemurafenib (formerly PLX4032) and metformin were tested against a panel of human melanoma cell lines with defined BRAF and NRAS mutations for effects on viability, cell cycle and apoptosis. Signaling molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 23 publications
11
55
0
1
Order By: Relevance
“…These results were confirmed by retrospective epidemiologic studies that reported a decrease in cancer risk in patients with diabetes treated with metformin (12). In addition, metformin was reported by several groups, including ours, to inhibit melanoma cell proliferation (13)(14)(15)(16). In our previous study, we showed that metformin dramatically impairs the growth of melanoma tumors in vitro and in vivo by inducing autophagic cell death leading to massive apoptosis (13).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results were confirmed by retrospective epidemiologic studies that reported a decrease in cancer risk in patients with diabetes treated with metformin (12). In addition, metformin was reported by several groups, including ours, to inhibit melanoma cell proliferation (13)(14)(15)(16). In our previous study, we showed that metformin dramatically impairs the growth of melanoma tumors in vitro and in vivo by inducing autophagic cell death leading to massive apoptosis (13).…”
Section: Introductionsupporting
confidence: 75%
“…For this purpose, using in vitro and in vivo approaches, we and others previously showed the potent effects of the antidiabetic drug metformin on reduction of melanoma cells growth and xenograft development (13)(14)(15)(16). One crucial step of melanoma development appears to be promotion of an EMT-like transition, a process having central role during RGP and VGP progression, melanoma invasion, and metastatic dissemination of melanoma cells (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that metformin efficiently suppresses the growth of various tumors, such as prostate carcinoma, and breast, lung and pancreatic cancer (11,12), which is in accordance with the results of a retrospective epidemiological study, showing a reduction in cancer risk in patients with diabetes who were receiving metformin (13). Furthermore, a number of studies have reported that metformin inhibits melanoma cell proliferation (14)(15)(16)(17).…”
Section: Introductionsupporting
confidence: 68%
“…A transformed cell adopting an "energy-saving" phenotype is unlikely to behave in an aggressive fashion, so a benefi cial cytostatic effect is plausible. However, in keeping with its evolutionary role, the activation of AMPK in certain contexts enhances survival (59)(60)(61). This may or may not have adverse clinical implications.…”
Section: Cellular Consequences Of Inhibition Of Oxidative Phosphorylamentioning
confidence: 99%
“…With VEGF inhibitors AMPK activation, which can be a consequence of metformin exposure, can lead to increased VEGF expression and enhanced survival under certain conditions. There is preclinical evidence that inhibition of VEGF expression synergizes with metformin exposure to reduce cancer growth and oppose prosurvival consequences of AMPK activation (59)(60)(61)(62).…”
Section: With Salicylatesmentioning
confidence: 99%